Obraz sąsiadów–zaborców w czasach stanisławowskich w świetle polskiej literatury pamiętnikarskiej - Rolnik, Dariusz (Przegląd Nauk Historycznych, 2005)
Apparently, in the eyes of the contemporaries, the picture of our neighbours-partitioners must have been univocally negative. Differences manifested themselves only in the range of malevolent attitudes towards each of them. In the literature of the subject the disposition of the citizens of the falling I Republic towards Russia, Prussia and Austria is presented automatically in the same way. No matter how true the thesis is it remains to some extent incomplete. In so far as there is no doubt about the generally negative views on the states and nations as a whole, oddly enough the approach towards individual representatives of those nations is positive. In that respect, the memoirs offer a somewhat different outlook upon neighbours-partitioners.In the majority of cases the enmity lessened when the sides got more closely acquainted, which can even be seen with the Polish exiles to Syberia. The positive and supposedly authentic and genuine opinions on the Russian or German, coming from the partitioning countries, appeared after the individual contact of the memoirist with a representative or the whole community of a given country while his previous records - from before the contact - fall within the canon of the generally negative stereotype of the given nation.In the Polish literature of king Stanislaus August times the view on the partitioning states seems apparently more univocal. They are all qualified as "despotic", depriving their citizens of freedom and liberties. A more profound analysis, though, of nuances present in the memoirists' records reveals their authors' longing for a calm and secure life, order, social justice and the authority of the state. As a matter of fact, the reforms of the Four-Years' Seym aimed to achieve that. Controversially, for many citizens of the fallen Republic the government systems of the partitioning states were not thoroughly unacceptable. Why, in the Russian partition, some did not even perceive the change of national status while in Prussia and Austria others saw a fair government system. In the same memoirs, however, there is nostalgia for the late glorious. strong, just and above all "our own" Republic.